Glass children: The lived experiences of siblings of people with a disability or chronic illness. (24th January 2022) - Hanvey, Imogen; Malovic, Aida; Ntontis, Evangelos
Abstract: Siblings of disabled or chronically ill children are often hidden family members and their needs for support might not be met. Current research however is limited in its understanding of siblings' lived experiences. This study uses semi‐structured interviews to explore the lived experiences of 16 individuals (referred to as siblings) who grew up with a disabled or chronically ill brother or sister. Participants reflected on their childhood and adolescent experiences as siblings, focusing on their social interactions and relationships, social support, and wellbeing. Using thematic analysis, we identified four distinct but theoretically related themes; participants experienced (a) feelings of invisibility during social interactions, (b) psychological difficulties due to the internalisation of family roles or life conditions, and (c) feelings of guilt and self‐blame. Finally, (d) social support was central as siblings were sometimes unable to understand their own needs, and support from family and peer groups helped them have their negative experiences validated. Our findings suggest greater support for siblings is required with a focus on addressing negative feelings and the availability of social support from people with similar experiences.